RIBA ANALYSIS IN BANK INTERESTVIEWED FROM THE PERSPECTIVE OF ISLAMIC LEGAL PHILOSOPHY - Titer Wahyanto; Yusuf Setyadi (ADISAM Publisher, 2022)
This study analyzes the controversy over bank interest including usury or not in the perspective of Islamic Law Philosophy. In this study found the problem of bank interest to date is still a polemic and an issue that is debated in society. This research is a qualitative research method that focuses on literature review. The study was conducted by collecting data that has relevance to the issues discussed, both from primary and secondary data. The primary data in this study refers to the works of experts who talk about bank interest and usury. While secondary data is in the form of writings including research documents and scientific journals that are related to the issues discussed. The law of usury in Islam is clearly forbidden. There are many hadiths and verses in the Al-Quran that explain it. As explained in Surah Al-Bawarah verses 275 and 278 and also mentioned in various Hadiths of Rasulullah SAW. However, regarding bank interest there is a difference of opinion among the scholars. Contemporary scholars differ on the law of bank interest, namely: 1) Some scholars, such as Yusuf Qaradawi, Mutawalli Sya'rawi, Abu Zahrah, and Muhammad al-Ghazali, stated that bank interest is illegal, because it includes usury. This opinion is also the opinion of forums of Islamic scholars including: Majma' al-Fiqh al-Islamy, Majma' Fiqh Rabithah al-'Alam al-Islamy, and the Indonesian Ulema Council (MUI). 2) Some other contemporary scholars, such as Syekh Ali Jum'ah, Muhammad Abduh, Muhammad Sayyid Thanthawi, Abdul Wahab Khalaf, and Mahmud Syaltut, emphasize that legal bank interest is permissible and does not include usury. This opinion is in accordance with the fatwa issued by Majma' al-Buhus al- Islamiyyah on 23 Ramadhan 1423 H, which coincides with 28 November 2002.